An acute papular eruption in an adolescent boy. (1st February 2022) - Lim, P. N.; Chopra, M.; Murphy, A.; Digby, S.; Aldworth, G.; Panarelli, M.; Christie, A.; Torley, D.
Abstract: Click https://wileyhealthlearning.com/#/online-courses/3a01300b-e9c7-4623-8621-35831713a993 for the corresponding questions to this CME article.